Ultrasound modalities and quantification: developments of multiparametric ultrasonography, a new modality to detect, localize and target prostatic tumors. Issue 3 (May 2015) - Postema, Arnoud; Idzenga, Tim; Mischi, Massimo; Frinking, Peter; de la Rosette, Jean; Wijkstra, Hessel
Abstract : Purpose of review: An imaging tool providing reliable prostate cancer (PCa) detection and localization is necessary to improve the diagnostic pathway with imaging targeted biopsies. This review presents the latest developments in existing and novel ultrasound modalities for the detection and localization of PCa. Recent findings: The ultrasound modalities that were very promising on introduction (HistoScanning and Doppler) have shown a wane in performance when tested in larger patient populations. In the meantime, novel ultrasound modalities have emerged in the field of PCa detection. Modalities, such as shear wave elastography (SWE) and contrast-enhanced ultrasound (CEUS) show very promising results. SWE produces an absolute elasticity measure and removes the need for manual compression of the tissue. The former allows comparison between scans and patients, the latter reduces the interoperator variability. Quantification of CEUS enables easily interpretable and accurate imaging of the microvascular changes associated with clinically significant prostate tumors. Summary: The novel ultrasound modalities of SWE and CEUS imaging open the door for taking targeted biopsies based on the detection and localization of PCa by these novel modalities. This potentially improves PCa detection wherein significantly reducing the number of biopsy cores.